Are school grades correlated with competencies in secondary school pupils with special needs? - Lange-Kuettner, Christiane (Frontiers in Education, 2024)
The current correlative study investigates whether and to what extent school grades are related to competencies in adolescents with and without special educational needs and disabilities (SEND) in inclusive secondary education. A sample of N = 2998 adolescents with a mean age of 12 years were longitudinally assessed in German language and Mathematics in a nationwide project on inclusive schooling in Germany in 2018/19 (T1) and 2019/20 (T2) in secondary school. The hypothesis was that competencies and school grades should be significantly correlated in both adolescents with and without SEND, showing the reliability of school grades for either group. Statistical analyses showed (1) all adolescents improved their competencies independently of their SEND status while school grades were moderately stable over time, (2) more variability of competencies and school grades emerged only at the tail ends of the scales of fail and best scores, (3) correlations between competencies and grades were consistently higher in mathematics than in German language for both pupils with and without SEND indicating a more objective and reliable measure.